Analysis of Village Fund Administration based on PMK Number 201/PMK.07/2022 in Evu Village, Southeast Maluku Regency - Dona Clarita Kadmaerubun; Lintje Kalangi; Lidia M. Mawikere (PT FORMOSA CENDEKIA GLOBAL, 2023)
Village fund management in PMK Number 201/PMK.07/2022 includes village fund administration consisting of the stages of receiving, saving, depositing/paying, administering, and accountability of village funds. This research was conducted to determine that the administration of village funds in Evu Village, Southeast Maluku Regency is in accordance with PMK Number 201/PMK.07/2022. The analytical method used in this research is a qualitative method with a descriptive approach whose data is obtained from interviews and documentation. The results of this research show that the village fund saving stage is in accordance with PMK Number 201/PMK.07/2022. Meanwhile, at the stage of receiving, depositing/paying, administering, and accountability of village funds, there are still several indicators that have not been carried out by the Evu Village government so that the administration of village funds is not fully in accordance with PMK Number 201/PMK.07/2022.